2018
DOI: 10.1007/s10461-017-2022-0
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Peer-Delivered HIV Testing and Counselling Among Men Who Have Sex with Men (MSM) and Transgender Women (TW) in Myanmar

Abstract: Men who have sex with men (MSM) and transgender women (TW) are a priority population for HIV prevention in Myanmar but report sub-optimal HIV testing frequency. Previous studies have shown that peer involvement in HIV testing can normalize stigmatized sexualities and reduce barriers to testing. We explored the acceptability of peer-delivered HIV testing among 425 undiagnosed MSM and TW in Yangon and Mandalay. An overwhelming majority of participants (86%) reported being 'comfortable/very comfortable' with peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Awareness of sexual orientation is an important precursor to provider-initiated HIV testing [36], and non-disclosure of sexual behaviours may hinder the provision of relevant and tailored sexual health information, including assessments of eligibility for biomedical HIV prevention options. Our findings corroborate reports of differential levels of HIV vulnerability and access to HIV services among sexual identities in Myanmar [4,11,23,29] and support the need for HIV prevention strategies tailored to the specific needs of MSM and TW sub -populations.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Awareness of sexual orientation is an important precursor to provider-initiated HIV testing [36], and non-disclosure of sexual behaviours may hinder the provision of relevant and tailored sexual health information, including assessments of eligibility for biomedical HIV prevention options. Our findings corroborate reports of differential levels of HIV vulnerability and access to HIV services among sexual identities in Myanmar [4,11,23,29] and support the need for HIV prevention strategies tailored to the specific needs of MSM and TW sub -populations.…”
Section: Discussionsupporting
confidence: 88%
“…While MSM and TW in Myanmar self‐report high levels of regular HIV testing , the dissonance with data presented in this paper may suggest an overestimation of testing behaviours among MSM or TW, or ongoing barriers to enacting testing aspirations. Documented barriers to HIV testing among MSM and TW in Myanmar include experiences of stigma and discrimination, perceived unfriendliness of government or mainstream health staff, and avoidance of HIV prevention services manifestly catering for MSM and TW among those for whom concealment of sexual identity is a key priority .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing literature emphasizes the importance of peer involvement in health promoting strategies among trans women, including peer-delivered HIV testing and counseling (Veronese et al, 2018) and peer education in HIV prevention (Silva-Santisteban, Eng, de la Iglesia, Falistocco, & Mazin, 2016). Although only half of participants in the formative phase of the study indicated the desire for a peer (trans woman) facilitator for the intervention, the feedback provided about the facilitator’s attentiveness, mastery, articulation, and communication skills were overwhelmingly positive.…”
Section: Discussionmentioning
confidence: 99%